Circ_0080425 inhibits cell proliferation and fibrosis in diabetic nephropathy via sponging miR‐24‐3p and targeting fibroblast growth factor 11 - Liu, Huifang; Wang, Xin; Wang, Zheng‐Yu; Li, Lingzhi (Journal of cellular physiology, 2020)
Diabetic nephropathy (DN) is a severe end‐stage kidney disease developed from diabetes mellitus. The involvement of circular RNAs (circRNAs) in modulating DN pathogenesis has been implied, but underlying mechanism is still lacking. In this study, we demonstrated that the expression of circ_0080425 correlated with the DN progression, and exerted positive effect on cell proliferation and fibrosis in mesangial cells. Further assessment suggested that circ_0080425 function as sponge harboring miR‐24‐3p. Moreover, miR‐24‐3p negatively correlated with the DN progression, and showed an antagonistic effect to circ_0080425on regulating MCs cell proliferation and fibrosis. Bioinformatics analysis predicted fibroblast growth factor 11 (FGF11) acting as direct downstream target of miR‐24‐3p. Indeed, the expression of FGF11 was significantly activated by circ_0080425 while suppressed by miR‐24‐3p. Knockdown of FGF11 resulted in a significant reduced cell proliferation rate and fibrosis. In addition, miR‐24‐3p inhibitor rescued the suppression of si‐circ_0080425 on FGF11, suggesting that circ_0080425 competitive binding to miR‐24‐3p could release FGF11 from miR‐24‐3p suppression, which subsequently promoted DN progression.In conclusion, we have reported a novel circ_0080425‐miR‐24‐3p‐FGF11 axis, and explored the underlying mechanism in regulating DN pathogenesis. The expression of circ_0080425 correlated with the diabetic nephropathy (DN) progression, and exerted positive effect on cell proliferation and fibrosis in mesangial cells. Circ_0080425 competitive binding to miR‐24‐3p could release FGF11 from miR‐24‐3p suppression, which subsequently promoted DN progression. In conclusion, we have reported a novel circ_0080425‐miR‐24‐3p‐FGF11 axis.